Japanese translation and linguistic validation of the Prosthetic Limb Users Survey of Mobility (PLUS-M). Issue 1 (22nd February 2022) - Balkman, Geoffrey S.; Samejima, Soshi; Fujimoto, Kazuki; Hafner, Brian J.
Abstract : Background: Self-report survey instruments can be used to improve clinical care for lower-limb prosthesis users on a global scale by pooling comparable health outcomes data from multiple countries. The language translation process is critical to the quality and comparability of a translated survey instrument. Objectives: The goals of this research were to translate the Prosthetic Limb Users Survey of Mobility (PLUS-M) item bank from English to Japanese using established guidelines, and linguistically validate the translated instrument by assessing its clarity, comprehension, and cultural applicability with Japanese prosthesis users. Study design: Instrument translation and qualitative interviews. Methods: The translation process included two forward translations, reconciliation, backward translation, and review by clinical experts in Japan. Adult lower-limb prosthesis users participated in a linguistic validation study by responding to translated survey items and providing item-by-item feedback through cognitive interviews. Results: Following expert reviews, translated items were classified as grammatically and contextually unchanged (n = 21), minor revision required (n = 19), major revision required (n = 3), or removed (n = 1). Cognitive interviews with 10 participants indicated that additional revisions were required (n = 4). Items were revised and retested until it was determined that they were clear, well understood, and culturally applicable. Conclusions: Use of a multistep translation and linguistic validation processes resulted in a linguistically comparable Japanese translation of the PLUS-M item bank. Japanese translations of the PLUS-M 7- and 12-item short forms were created for use in clinical practice and research. Availability of these linguistically comparable instruments is expected to facilitate opportunities for international comparison of prosthetic mobility data.